The pathogen of Milk Thistle (Silybum marianum (L.) Gaertn.) in the Czech Republic (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Milk thistle is grown in the Czech Republic as a medicinal herb; silymarin is isolated from its achenes and used for the production of liver and gallbladder medicine. The quality and content of the active compound is influenced not only by environmental factors, but also by pests and pathogens. The occurrence of pests of milk thistle variety Silyb was observed in two localities during the years 2011 2013. In the year 2011 the mycoflora of seeds of four milk thistle varieties was determined. Representatives of 15 species were isolated from the seeds, most of them saprophytic. 21 fungal species were isolated and identified from milk thistle plants during the vegetation; Septoria silybi among the most important ones. Possibilities of protection of milt thistle against pathogens are discussed.